Web-based Application Mockup Design for Student Activity Unit Registration at Mercu Buana University - Andrean, Rifky; Soemantri, Syauqi Adli; Salamah, Umniy; Arrachman, Abdul Kholiq (Journal Collabits, 2025)
The development of the Student Activity Unit (UKM) registration application aims to streamline the registration process for students interested in joining extracurricular activities at educational institutions. This application offers a digital solution to replace the manual registration process, improving efficiency, data accuracy, and user experience.The design and implementation of the application follow a systematic approach, including needs analysis, system design, coding, testing, and deployment. The application features a user-friendly interface, secure data management, and real-time notifications, ensuring a seamless experience for both students and administrators.By integrating cloud-based technology, the application ensures scalability and accessibility, allowing users to register anytime and anywhere. Administrators can manage registrations, track member data, and generate reports more effectively. The study results show that the application significantly reduces administrative workload and enhances the engagement of students in UKM activities.This project highlights the potential of digital solutions in improving operational processes and fostering student participation in extracurricular activities. Future developments may include expanding features such as online payment integration and analytics for tracking member participation trends.